Study on the influencing factors of childcare needs and their operation mechanism among parents with children aged 0–3 years in China—an empirical analysis based on a mixed methods study - Li, Huanhuan; Duan, Bingyu; Zhang, Yuhuan; Chen, Mingci; Wang, Yifang; Di, Huijuan (Frontiers in Public Health, 2025)
BackgroundExploring and analyzing the factors influencing parents’ demand for childcare is essential for improving the quality of childcare services. However, there is a lack of empirical studies that effectively explore the factors influencing demand for childcare and its mechanisms of action. Therefore, this study used a mixed research method to explore the factors influencing demand for childcare and their mechanisms of action.MethodsSemi-structured interviews were conducted with 63 participants including parents of 0–3-year-old children, childcare center administrators, teachers, education specialists, and community members. Second, three levels of coding of the interview data using Grounded Theory were used to summarize the factors influencing parents’ childcare needs. Third, we combined relevant theories to construct a theoretical model of the factors influencing parents’ childcare services for children aged 0–3 years old and formulated research hypotheses. Fourth, the study used the “Questionnaire on the Childcare Needs of Parents of Children Aged 0–3″ to survey 516 parents. We analyzed and tested the constructed theoretical model through regression and mediation analyses.ResultsThe Grounded Theory results found that factors influencing the childcare needs of parents of infants and toddlers aged 0–3 years include Childcare Center Management, Teacher Professionalism, Environment and Facilities, Health Care Services, and Educational Activities. Mediating effect analyses revealed that (1) Childcare Center Management and Teacher Professionalism positively and directly influenced Educational Activities. (2) Health Care Services is mediated between Childcare Center Management and Educational Activities, and Health Care Services is mediated between Teacher Professionalism and Educational Activities. (3) Environment and Facilities and Health Care Services are chained between Childcare Center Management and Educational Activities, Teacher Professionalism and Educational Activities.ConclusionChildcare-related organizations should improve the quality of Childcare Center Management, Teacher Professionalism, Environment and Facilities, Health Care Services, and Educational Activities to eliminate parents’ childcare concerns and meet their childcare needs.